Response of Adrenal Catecholamine to a Newly Synthesized Chemical Radioprotector - Hasan, S. S.; Mazumdar, S.; Singh, P.M.; Pandey, S.N. (Nuklearmedizin - NuclearMedicine, 1981)
This study was undertaken to try a newly synthesized compound (1-acetyl hydrazinyl thiophenyl formamidine dihydro-chloride) as a chemical radioprotector and to observe its effects on adrenal catecholamine and protein bound iodine (PBI). After whole-body irradiation, the catecholamine and serum PBI levels decreased significantly but treatment with the drug before irradiation increased the same. The whole-body irradiation resulted in a 50% mortality within a fortnight whereas the use of the drug prevented it.